Bimbingan Pengembangan Teknis Program Pembelajaran Praktikum SMK Di SMK Adimulia Batam - Rosie Oktavia Puspita Rini; tirta Mulyadi; Agung Arif Gunawan; Miratia Afriani; Wahyudi Ilham (JURNAL KEKER WISATA, 2023)
This article includes research findings exploring how vocational education institutions should play their best role in preparing graduates for the world of work. The aim of this study is to provide an element for vocational education to meet the growing demand. This research uses the literature review method by deepening the literature and previous research results. The research aims to answer two questions, namely what is the current status of vocational training and what needs to be done to improve the quality of vocational training, especially in the face of advances in science and technology in the era of the industrial revolution 4.0. . The conclusion of this study is that there are still things that can be improved such as increasing the capacity of professional teachers, increasing synergy and pentahelix collaboration, revitalizing professional education with more experts. educational machinery, rebranding through direct research to industry and comparative in more advanced educational institutions both at home and abroad, while adding personality to students. Therefore, it is hoped that vocational education can participate in real efforts to implement government programs aimed at advancing Indonesia by preparing superior human resources.